Data Warehouse Design With ETL Method (Extract, Transform, And Load) for Company Information Centre - Fana, Wulan Stau; sovia, rini; Permana, Randi; Islam, Md Ataul (Universitas Dharma Wacana, 2021)
Data Warehouse is a technology use to analyze, extract and evaluate data into information which produce knownledge in the form of analysis to provide an advice in decision making process. Designing a Data Warehouse using ETL (Extract, Transformation and Load) process serves as the collection of data from different data sources into a multitude of integrated data sets. By using snowflake scheme for the design of the data warehouse make data prepare well and ready for analyze on Data Warehouse. The result of Â this reseach is to applied Data Warehouse that use to support company decision making progress make easier and has a good decision since its come from Data Warehouse